Symbolic interpretation of sea songs and shanties in sea travel writing: A myth-analytical approach - Garcés García, Pilar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Travel writing is characterized by a narrative discourse that describes landscapes, transforms adventure into a mythical journey and reveals the fears of humankind. The sea gathers momentum when the protagonists overcome the fear of death. However, the significance of the tune of sea songs has not been adequately highlighted, being relegated as side special effects that embellish the narration. The aim of this paper is to analyze the symbolical element of the songs to foreground its function in sea travel writing in the English and American fiction from the 18th to the 21st century accounts, and their symbolic implication.